Contrastive Analysis Of Adjective Reduplication In Indonesian And Chinese - Li Yan Ying; Suroso (Cita konsultindo, 2025)
This study aims to describe the similarities and differences in adjective reduplication forms between Indonesian (BI) and Mandarin (BM). The method applied in this study is descriptive qualitative research with a contrastive analysis approach. Data were collected through literature review and documentation methods, and subsequently analyzed morphologically. The results reveal similarities in the “AA” reduplication pattern found in both languages. However, notable differences were also identified. Mandarin has polysyllabic adjective reduplication forms categorized into several distinct patterns, namely “ABB,”